Sistem Informasi Penyaluran Donasi Berbasis Web - Fabriyan Fandi Dwi Imaniawan (Indonesian Journal on Software Engineering (IJSE), 2020)
Abstract: The implementation of information system is absolutely important for an institution or social organization in the millennial era. Media is needed to fulfill perceived social needs for information and services, such as a website. For an institution or social organization, the website currently has an important role. In terms of online donations distribution, website is required for conveying information and creating donation services to the donor through internet access or by online. The manual acceptance and distribution donations are the existing problems in transaction management. Therefore transparency on the donation report is still limited and requires a long time process. This causes a slow process of making reports because of the many unconfirmed donations. In this research, a web-based donation distribution system is created using the waterfall method, starting from software analysis, design, program code creation, testing to maintenance. The system is expected to manage processss from receiving transactions to distributing donations effectively and efficiently, resulting to a transparent financial report for donors.Keywords: Donation, Social Organization, WebsiteAbstrak: Penerapan sistem informasi pada era millenial saat ini sangat penting dilakukan bagi sebuah lembaga ataupun organisasi sosial. Diperlukan adanya media untuk memenuhi kebutuhan akan informasi dan layanan, seperti website. Bagi sebuah lembaga maupun organisasi sosial, website saat ini memiliki peran yang penting. Misalnya, dalam hal penyaluran donasi perlu adanya media website untuk membantu dalam menyebarkan informasi dan membuka layanan donasi untuk para donatur melalui internet atau secara online. Permasalahan yang muncul selama ini terdapat di dalam pengelolaan transaksi donasi yang masih manual sehingga membutuhkan waktu yang lama. Hal ini menyebabkan lambatnya proses pembuatan laporan karena banyaknya donasi yang belum terkonfirmasi. Dalam penelitian ini, dibuatlah sistem penyaluran donasi berbasis web menggunakan metode waterfall, mulai dari analisa perangkat lunak, desain, pembuatan kode program, pengujian dan pemeliharaan. Diharapkan dengan adanya sistem ini, pengelolaan dari transaksi penerimaan hingga penyaluran donasi dapat lebih efektif dan efisien sehingga berpengaruh kepada pembuatan laporan keuangan yang dapat dipertanggungjawabkan secara transparan kepada donatur.Kata kunci: Donasi, Organisasi Sosial, Website